GENETIC DIVERSITY OF RAPESEED (Brassica napus L.) GENOTYPES IN BANGLADESH (Bangladesh Journal of Plant Breeding and Genetics, 2017)
Genetic diversity in thirty eight traditional rapeseed genotypes was studied under favorable condition through Mahalanobis D2 statistic for yield and yield contributing characters. The genotypes were grouped into five clusters. The inter-cluster distances were higher than intracluster distances indicating wider genetic diversity among the clusters. The intra-cluster distances were lower in all the cases reflecting homogeneity of the genotypes within the clusters. Among the different cluster the genotypes of the cluster IV, III and I included were taller plant. The genotypes in the cluster III and IV had large size raceme. The genotypes in the cluster IV, III and V exhibited comparatively higher number of siliqua per raceme. Longer siliqua was noticed for the genotypes in the cluster III, IV and I. Higher number of seeds per siliqua noticed in clusters I, II and III. The genotypes of the cluster I and II produced bold size seed. The genotypes in the cluster V and I had high harvest index. The genotypes of the cluster III and I produced high seed yield per plant. Among the different cluster, the cluster III included the genotypes which had high yield, higher number of seeds per siliqua, longer siliqua, siliqua number per raceme and high plant height. Moreover these cluster displayed wide divergence with the genotypes of cluster V. The genotypes of the cluster V had the highest harvest index therefore selection of the parental material for crossing program for improvement of yield in rapeseed is suggested from these two clusters.